“Impact of Bonus Issue on Share Prices of Indian Pharmaceutical Companies” (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The foremost purpose of this paper is to analyse  the impact of the bonus issue on the price  of the share of the company. This paper will  also appraise the impacts of the price of share  by the distribution ratio of bonus shares of  pharmaceutical companies. For these study 32  pharmaceutical companies listed in National  Stock Exchange & Bombay Stock Exchange  has taken which dispersed the bonus issues to  its shareholders over the period of 10 years.  The sample size of the paper is 32 Indian  pharmaceutical companies. The simple random  technique has been used by the researchers as a  sampling technique for the study and the paper  is based on secondary data. The study reveals that the stock price of most  of the companies rises next day of bonus issue  announcement day. Many pharmaceutical  companies distributed bonus shares in the ratio  ofmore than or equal to 100 percent responses  positively in the study. This study shows that  around 65.62 % pharmaceutical companies  responses optimistic to the stock prices of  the respective stock next day of the bonus  announcement. The study also demonstrates  that around 43.75% pharmaceuticals companies  whose distribution ratio of bonus share is more  than or equal to 100 percent deliver a positive  return. The highest number of pharmaceutical  companies declares the bonus issue in 2013.
Keywords: Announcement of bonus shares; Bonus Ratio; Corporate actions, Impact on Share Prices; Indian Pharmaceutical Companies; T-test